Predictive Value of Hepatic Venous Pressure Gradient for Graft Hemodynamics in Living Donor Liver Transplantation. Issue 7 (2nd May 2019) - Matsushima, Hajime; Fujiki, Masato; Sasaki, Kazunari; Rotroff, Daniel M.; Sands, Mark; Bayona Molano, Maria Del Pilar; Aucejo, Federico; Diago Uso, Teresa; Eghtesad, Bijan; Miller, Charles; Quintini, Cristiano; Hashimoto, Koji
Abstract : The hepatic venous pressure gradient (HVPG) measurement is known to correlate with the severity of portal hypertension in patients with liver cirrhosis. This retrospective study investigated the clinical value of preoperative measurement of HVPG in patients who underwent adult‐to‐adult living donor liver transplantation (LDLT) and its predictive value for hepatic hemodynamics after graft reperfusion. For this study, 75 patients who underwent adult‐to‐adult LDLT were divided into 2 groups (HVPG <16 mm Hg or HVPG ≥16 mm Hg) to investigate the correlation between preoperative HVPG and characteristics and surgical outcomes of the patients, including portal vein flow (PVF) and hepatic artery flow (HAF) after graft reperfusion. In total, 35 (46.7%) patients had an HVPG ≥16 mm Hg. These patients had significantly higher international normalized ratio values, serum creatinine levels, and Model for End‐Stage Liver Disease scores compared with the 40 patients with HVPG <16 mm Hg. They also had higher rates of variceal bleeding, encephalopathy, and intractable ascites as well as lower serum albumin levels and platelet counts compared with those patients with HVPG <16 mm Hg. Portal inflow modulation (PIM) was frequently performed in the patients with HVPG ≥16 mm Hg compared with those with HVPG <16 mm Hg. No significant differences in surgical outcomes after LDLT were found between these 2 groups except for postoperative ascites. Preoperative HVPG showed a positive correlation with PVF and a negative correlation with HAF after graft reperfusion (false discovery rate [FDR] P  = 0.08 and FDR P  = 0.08, respectively). In linear regression analyses, preoperative HVPG was independently associated with PVF after graft reperfusion. In conclusion, our findings indicate that preoperative HVPG is associated with hepatic hemodynamics after graft implantation in LDLT. HVPG as a routine preoperative evaluation may be helpful for surgical planning of PIM.